2015
DOI: 10.2196/mhealth.3672
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Far Side of Mobile Health: Information Security and Privacy of Mobile Health Apps on iOS and Android

Abstract: BackgroundMobile health (mHealth) apps aim at providing seamless access to tailored health information technology and have the potential to alleviate global health burdens. Yet, they bear risks to information security and privacy because users need to reveal private, sensitive medical information to redeem certain benefits. Due to the plethora and diversity of available mHealth apps, implications for information security and privacy are unclear and complex.ObjectiveThe objective of this study was to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(167 citation statements)
references
References 81 publications
1
164
0
2
Order By: Relevance
“…These details are also often open to data security and privacy breaches. Health, medical and fitness apps in general are notorious for leaking personal data and failing to encrypt data effectively [23,24]. One study found that only one in three pregnancy and parenting apps has implemented a security mechanism to guarantee privacy and confidentiality of the data that people were uploading [25].…”
Section: Introductionmentioning
confidence: 99%
“…These details are also often open to data security and privacy breaches. Health, medical and fitness apps in general are notorious for leaking personal data and failing to encrypt data effectively [23,24]. One study found that only one in three pregnancy and parenting apps has implemented a security mechanism to guarantee privacy and confidentiality of the data that people were uploading [25].…”
Section: Introductionmentioning
confidence: 99%
“…(8,9) One study identified potential data security and privacy breaches in 95.63%, 17,193/17,979 of mobile iOS apps. (10) In our project, patient confidentiality and data security were built into the design from the beginning, starting with the hospital firewall for data repository and with the use of protected institutional emails.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to develop peer-review systems of medical Apps or CDSS assessing expert medical involvement and adherence of content to current guidelines as Health Apps Library, developed by the National Health Service in the United Kingdom [19]. Furthermore, the scores obtained by HTE-DLPR in the security area of QoE reflect the extreme importance that users give to safety of storing clinical data, in order to ensure patient confidentiality [20]. It may be the case that HTE-DL-PR administrator update requirement resulted in a decreased user confidence regarding its security.…”
Section: Discussionmentioning
confidence: 99%